PELATIHAN APLIKASI SURAT MENYURAT DAN LAPORAN KEUANGAN KAS RT.05 RW.01 KELURAHAN CIPAYUNG JAYA KOTA DEPOK - Wahyudi, Dedy; Jamain , Tries Handriman; Hamdanur, Peris; Zuhrofi , Ahmad (Jurnal Pengabdian Bukit Pengharapan, 2024)
In the area that is a partner for community service activities, which is located in the RT in the area RT.05, RW.01, Cipayung Jaya Village, Cipayung District, Depok City, the management is not good in serving administrative activities for the local community, namely in processing correspondence and other than The Partner does not understand about Cash Financial Reports where partners still carry out Cash Financial Reports manually, namely in the form of writing in ledgers, difficulties in searching for data, loss of data, reporting financial cash still using handwriting and file damage. The solution that can be provided to overcome partner problems is that counseling and training activities need to be held for the administrators of RT.05, RW.01, Cipayung Jaya Village, Cipayung District, Depok City in terms of making correspondence through and Cash Financial Reports using MS Word and MS Excel applications. to make it easier and more structured. This community service activity provides a good solution for partners, namely the administrators of RT.05, RW.01, Cipayung Jaya Village, Cipayung District, Depok City, by using information technology to provide socialization and training on the use of Correspondence Applications and Cash Financial Reports, so as to improve quality. local RT/RW management services, especially in managing correspondence and Cash Financial Reports via MS Word and MS Excel applications effectively. The result of this service activity is that there is an increase in knowledge and skills by 67.5%. The implementation of the service went smoothly and the participants were very enthusiastic about participating both in terms of attendance and in conveying questions and experiences in making it related to making correspondence and cash financial reports using MS Word and MS Excel applications.